Seven-Year Visual and Anatomical Outcomes of Intravitreal Vascular Endothelial Growth Factor Inhibition for Neovascular Age-Related Macular Degeneration - Martin Stattin; Julia Forster; Daniel Ahmed; Anna-Maria Haas; Alexandra Graf; Katharina Krepler; Siamak Ansari-Shahrezaei (Journal of Ophthalmology)
Purpose. To evaluate 7-year visual and anatomical outcomes of intravitreal injections (IVI) with antivascular endothelial growth factor (anti-VEGF) for neovascular age-related macular degeneration (nAMD) based on a personalized pro re nata (PRN) regimen. Methods. Anonymized data of 124 consecutive eyes in 121 patients with treatment-naïve nAMD were initially collected in 2010. Of those, 45 received anti-VEGF IVI at least every 6months until 2017 in one single center in Austria and hence were retrospectively analyzed. All eyes had been initiated on a loading dose of 3 monthly IVI with different anti-VEGF agents followed by a PRN regimen in the first year. At year 2, monitoring as well as therapeutic intervention could be prolonged every 2weeks up to intervals of 3months without capping treatment. Primary outcome measure was the change of visual acuity (VA) assessed by Early Treatment Diabetic Retinopathy Study charts at 4 meters (ETDRS) in letters—counting every correctly read letter—and converted to Snellen. Secondary outcome measures were number of injections and change of central retinal thickness (CMT) from baseline. Results. Mean baseline VA was 20/63 + 1 (0.63 ± 0.26 ETDRS) and declined to 20/100 + 2 (0.45 ± 0.33) with an overall loss of 9 letters ETDRS after 7years (p = 0.001). An average of 3.5 ± 1.9 IVI was given per year and eye. Mean CMT at baseline was 322 ± 95 μm, decreased by 52 μm to 270 ± 70 μm within the first year, and remained below baseline at year 7 (271 ± 106 μm; p<0.001). Conclusions. Our data confirm an absolute vision loss in eyes compromised by nAMD after 7 years of continuous VEGF inhibition. The visual decline was significantly related to baseline VA as well as the number of injections. We suggest following patients thoroughly independent of the initial VA and a greater incentive for the physician to treat.